Ecological corridors in Costa Rica: An evaluation applying landscape structure, fragmentation-connectivity process, and climate adaptation - Morera Beita, Carlos (2021)
In recent years, ecological corridors have been proposed on a global scale as a response to the accelerated process of natural ecosystem fragmentation, mainly as a result of human impact. In accordance with this trend, Costa Rica has undergone a process of implementing ecological corridors as to promote ecological connectivity since the 1990s, with the establishment of 44 ecological corridors covering 38% of Costa Rica's territory. Nevertheless, there is no research evaluating these corridors on a national scale that takes into account their functions as conduits, barriers, and habitats. Thus, the objective of this research was to describe the process of biological corridor formation in Costa Rica, and to evaluate the potential effectiveness of corridors by considering aspects of landscape structure and ecological processes related to connectivity and fragmentation. We used the National Program of Ecological Corridors database along with coverage analysis from Landsat images from 2000 and 2015.The composition of the biological corridors was determined at the landscape scale and related to potential to maintain a specific population of wild mammals weighing more than 10 kg. The composition of the ecological corridors was highly variable in terms of total area, proportion of natural habitat, and fragmentation process. Most biological corridors are capable of maintaining viable populations of Pecari tajacu and Tapir bairdii, while none could maintain populations of Panthera onca and Tayassu pecari. Only 50% of the biological corridors had improved in their connectivity. Therefore, public policies, such as master plans focusing on ecosystem restoration must be established. In addition, only two biological corridors incorporate the majority of elevation ranges (Life Zones) present in the country, which reduces the potential of the corridor system as a tool for climate change adaptation.